Palenie tytoniu i spożywanie alkoholu przez młodzieży ponadgimnazjalną Zespołu Szkół Chemicznych w Bydgoszczy = Smoking and alcohol consumption by high school youth of the School of Chemistry in Bydgoszcz - Pluta, Agnieszka; Jaczek-Kierzenkowska, Jolanta; Faleńczyk, Kamila; Budnik-Szymoniuk, Maria; Basińska-Drozd, Halina; Marzec, Alicja (Journal of Education, Health and Sport, 2016)
Pluta Agnieszka, Jaczek–Kierzenkowska Jolanta, Faleńczyk Kamila, Budnik‑Szymoniuk Maria, Basińska-Drozd Halina, Marzec Alicja. Palenie tytoniu i spożywanie alkoholu przez młodzieży ponadgimnazjalną Zespołu Szkół Chemicznych w Bydgoszczy = Smoking and alcohol consumption by high school youth of the School of Chemistry in Bydgoszcz. Journal of Education, Health and Sport. 2016;6(8):21-27. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.59613 http://ojs.ukw.edu.pl/index.php/johs/article/view/3723 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.07.2016. Revised 25.07.2016. Accepted: 28.07.2016. Palenie tytoniu i spożywanie alkoholu przez młodzieży ponadgimnazjalną Zespołu Szkół Chemicznych w Bydgoszczy Smoking and alcohol consumption by high school youth of the School of Chemistry in Bydgoszcz Agnieszka Pluta1, Jolanta Jaczek–Kierzenkowska2, Kamila Faleńczyk1, Maria Budnik‑Szymoniuk1, Halina Basińska-Drozd1, Alicja Marzec1 1Zakład Pielęgniarstwa Społecznego, Wydział Nauk o Zdrowiu Uniwersytetu Mikołaja Kopernika w Toruniu Collegium Medicum w Bydgoszczy 2WOZ "GRYF-MED" w Bydgoszczy 1Department of Community Nursing Faculty of Health Sciences Collegium Medicum in Bydgoszcz of the Nicolaus Copernicus University in Toruń 2WOZ”GRYF-MED” In Bydgoszcz Słowa kluczowe: palenie tytoniu, spożycie alkoholu, młodzież szkolna, szkoła ponadgimnazjalna. Keywords: tobacco smoking, alcohol, youth, senior high school. Abstract Introduction. Smoking and alcohol consumption are the most common risky behaviors undertaken by young people. These behaviors determine the state of health of the younger generation and also future parents. Material and methods. The study included the number of 100 students in grades matriculation of the School of Chemistry in Bydgoszcz. The work as a research tool used by his own questionnaire. Objective. The aim of the study was to analyze the prevalence of smoking and alcohol use among high school youth, final award of the School of Chemistry in Bydgoszcz. Results. Youth male accounted for most of the study group - 54 persons (54.0%). The vast majority of 66 persons (66%) did not smoke cigarettes. Among smokers the highest percentage of pupils 18 (52.9%) declared burning cigarettes less than a pack a day. Alcohol consumption was declared by 83 students (83%), of which the largest percentage of 42% only occasionally. Conclusions. It was found a high prevalence of smoking and alcohol consumption among adolescents final award of the School of Chemistry in Bydgoszcz. Smoking and alcohol consumption was more prevalent among young males living in rural areas. Streszczenie Wprowadzenie. Palenie tytoniu i spożywanie alkoholu to najczęstsze zachowania ryzykowne podejmowane przez młodzież. Zachowania te warunkują stan zdrowia młodego pokolenia i jednocześnie przyszłych rodziców. Materiał i metoda. Badaniami objęto liczbę 100 uczniów klas maturalnych Zespołu Szkół Chemicznych w Bydgoszczy. W pracy jako narzędzie badawcze wykorzystano kwestionariusz ankiety własnego autorstwa. Cel. Celem pracy była analiza występowania palenia tytoniu i spożywania alkoholu wśród młodzieży ponadgimnazjalnej, maturalnej Zespołu Szkół Chemicznych w Bydgoszczy. Wyniki. Młodzież płci męskiej stanowiła większość w badanej grupie – 54 osoby (54,0%). Zdecydowana większość 66 osoby (66%) nie paliła papierosów. Wśród palących największy odsetek uczniów 18(52,9%) deklarował wypalanie papierosów mniej niż paczki dziennie. Spożywanie alkoholu deklarowało 83 uczniów (83%) z czego największy odsetek 42% tylko okazjonalnie. Wnioski. Stwierdzono wysokie rozpowszechnienie palenia papierosów i spożywania alkoholu wśród młodzieży maturalnej Zespołu Szkół Chemicznych w Bydgoszczy. Palenie papierosów i spożywanie alkoholu częściej rozpowszechnione było wśród młodzieży płci męskiej mieszkającej na wsi.